A Content Analysis of Polemics in a Regulation Regarding Sexual Violence on Campus - Rona Rizkhy Bunga Chasana; Putri, Devi Afriyantari Puspa; Vernanda, Yuniar (UPT Publikasi Ilmiah UNISBA, 2023)
The government hopes that the release of the Minister of Education and Culture Regulation concerning the Prevention and Handling of Sexual Violence (Permendikbudristek PPKS) No. 30 of 2021 can address the problem of sexual violence on campus. However, this regulation sparked debate among various parties who disagreed with the phrase